2015
DOI: 10.1002/jssc.201500899
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in lipidomics for disease research

Abstract: Lipidomics is an important branch of metabolomics, which aims at the detailed analysis of lipid species and their multiple roles in the living system. In recent years, the development of various analytical methods for effective identification and characterization of lipids has greatly promoted the process of lipidomics. Meanwhile, as many diseases demonstrate a remarkable alteration in lipid profiles compared with that of healthy people, lipidomics has been extensively introduced to disease research. The compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 157 publications
2
60
0
Order By: Relevance
“…19, 20 Indeed, recent lipidomics studies revealed a dynamic alteration of the membrane lipid composition in human cancer tissues, 21 and distinct lipid profiles correlated with tumor grade. 22 Moreover, combination of molecular biology and lipidomics techniques revealed some of the mechanisms underlying deregulated lipid metabolism in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…19, 20 Indeed, recent lipidomics studies revealed a dynamic alteration of the membrane lipid composition in human cancer tissues, 21 and distinct lipid profiles correlated with tumor grade. 22 Moreover, combination of molecular biology and lipidomics techniques revealed some of the mechanisms underlying deregulated lipid metabolism in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…atherosclerosis), neurodegenerative disease (e.g. Alzheimer’s disease) and infection disease, have been well summarized in other reviews[3,57]. In the past few years, the application of lipidomics to studies of skin biology and inflammatory skin diseases has drawn particular attention.…”
Section: Introductionmentioning
confidence: 99%
“…Lipidomics is an important branch of metabolomics, which has been extensively introduced to many diseases research, including diabetes mellitus and atherosclerosis [6]. As lipids can be divided into eight categories (fatty acyls, glycerolipids, glycerophospholipids, sphingolipids, sterol lipids, prenolipids, saccharolipids, and polyketides) containing distinct classes and subclasses [7], and each class of lipids contains a series of molecules with different combination of acyl chains, the diversity of lipids presents a challenge in lipidomics analysis [8].…”
Section: Introductionmentioning
confidence: 99%